2016
DOI: 10.1038/mp.2016.53
|View full text |Cite
|
Sign up to set email alerts
|

Methylomic changes during conversion to psychosis

Abstract: The onset of psychosis is the consequence of complex interactions between genetic vulnerability to psychosis and response to environmental and/or maturational changes. Epigenetics is hypothesized to mediate the interplay between genes and environment leading to the onset of psychosis. We believe we performed the first longitudinal prospective study of genomic DNA methylation during psychotic transition in help-seeking young individuals referred to a specialized outpatient unit for early detection of psychosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 52 publications
(54 reference statements)
3
40
1
2
Order By: Relevance
“…The need for longitudinal studies is therefore crucial in this field. Recently, Kebir et al have published a pioneering longitudinal prospective study, based on a cohort of help‐seeking young individuals enrolled for a 1‐year follow‐up. They showed that specific changes in DNA methylation are significantly different between converters to psychosis and non‐converters in SCZ, and occur in a clustered manner, preferentially in genes belonging to pathways relevant for psychosis (oxidative stress regulation, axon guidance and inflammatory pathways).…”
Section: Discussionmentioning
confidence: 99%
“…The need for longitudinal studies is therefore crucial in this field. Recently, Kebir et al have published a pioneering longitudinal prospective study, based on a cohort of help‐seeking young individuals enrolled for a 1‐year follow‐up. They showed that specific changes in DNA methylation are significantly different between converters to psychosis and non‐converters in SCZ, and occur in a clustered manner, preferentially in genes belonging to pathways relevant for psychosis (oxidative stress regulation, axon guidance and inflammatory pathways).…”
Section: Discussionmentioning
confidence: 99%
“…There is also an increasing number of genome-wide DNAm profiling studies of non-central nervous system (CNS) tissues such as blood (12,13,(48)(49)(50)(51)(52)(53) and saliva (54) ( Table 2). These can be further subdivided into longitudinal studies (48)(49)(50)(51)54), which assessed markers of conversion to psychosis in twins discordant for schizophrenia or high-risk individuals, and biomarker studies (12,13,52,53), which aim at uncovering biomarkers for schizophrenia in large cohorts. One advantage…”
Section: Dna Methylationmentioning
confidence: 99%
“…Such longitudinal investigations, however, will require the use of easily accessible tissues such as peripheral blood, saliva, and olfactory epithelium (149). Even if epigenetic signatures in peripheral tissues might not necessarily capture disease-associated epigenetic changes occurring in the CNS (Tables 1 and 2), they can provide valuable information regarding the clinical course of schizophrenia, including conversion from a high-risk state to first-onset psychosis (50). The complementary use of animal models will further aid the interpretation of epigenetic findings obtained from longitudinal studies in humans.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…To address this issue, the use of analytical methods (e.g. causal inference testing and Mendelian randomization) or methodological approaches, such as the use of longitudinal cohorts would greatly help in deciphering the epigenetic contribution to disease. Finally, the use of adequate experimental models in rodents or in vitro systems, such as human inducible pluripotent cells derived from patients, in combination with an epigenome‐editing approach, could open new avenues to unravel the biological relevance of epigenetic changes.…”
Section: Current Challenges In Epigenetic Studies and Future Perspectivementioning
confidence: 99%